FORMULATION AND EVALUATION OF LUMEFANTRINE CAPSULE PREPARED BY USING LIQUISOLID TECHNIQUE - Khan, Amreen; Agrawal, Shikha (International Journal of Current Pharmaceutical Research, 2018)
Objective: The objective of present research work was to formulate and evaluate of Lumefantrine capsule by using novel liquisolid technique to give increased dissolution rate of poorly water-soluble drug Lumefantrine. Methods: Formulation of lumefantrine capsule using drug solution and suspension method was used. Different liquisolid formulations were prepared using a mathematical model for calculating required quantities of powder and liquid ingredients to produce an acceptably flowable and compressible admixture. Liquisolid capsule formulation F-1 to F-9 were prepared by using different type and different concentration of non-volatile solvent like PEG-400, Tween 80, propylene glycol and avicels, aerosil as carrier and coating material respectively. Results: The liquisolid formulation were within the acceptable limits and drug release rates of all prepared liquisolid were distinctly higher as compared to pure drug. Lumefantrine shows maximum solubility in tween 80 as a non-volatile solvent. All the preformulation parameters were evaluated such as organoleptic characterization of the drug sample, melting point, pH, identification of drug samples by using UV spectroscopy and FTIR analytical method, preparation of calibration curves, solubility studies of drug sample like qualitative, quantitative and pH-dependent solubility of the drug in a buffer solution of different pH. They were further processed for solid-state characterization such as, DSC and SEM and the results confirmed the transformation of native crystalline nature of drug to an amorphous state. FTIR analysis also confirmed no drug-excipient interaction. Liquisolid formulations showed improved in vitro dissolution behaviour of lumefantrine over that of pure drug. Conclusion: From this study, it was concluded that liquisolid method is a promising alternative for improvement of dissolution property of water-insoluble drugs.